If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 + 7n = 36 Solving -15 + 7n = 36 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 7n = 36 + 15 Combine like terms: -15 + 15 = 0 0 + 7n = 36 + 15 7n = 36 + 15 Combine like terms: 36 + 15 = 51 7n = 51 Divide each side by '7'. n = 7.285714286 Simplifying n = 7.285714286
| 2(x-5)(x-5)+6=22 | | 418=-7(4+8n)-2 | | 5-x/6=5 | | (4x+9)(5x+5)= | | 6y-61=y+14 | | 11/17x=5 | | (5x^4+3xy-y^3)-(x^4+9xy-3y^3)= | | 3x+7+2x-7=180 | | 1/2×-6/15 | | 15-17x=49 | | 7-9x+15=3x+22-12x | | 12+23p=100 | | 1/3x1-5/3 | | 2x^2+4=-14-x^2 | | 12-6n=30 | | -1.4x+0.6y=10 | | log[7](3x+6)=3 | | 2(y+3)=3(y-5) | | 42-6x=114 | | C/3-3=3 | | 19-2x=-19 | | 2(1+8x)+7=-103 | | -5-4x=35 | | 4r(6-7a)=2c | | 5x-4=-39 | | B/p-a/P=1 | | -3x-16=29 | | 7y+3x=105 | | V=(4/3)3.14r•3 | | x/6-5=-4 | | x+y*x=65 | | -3n-4=28 |